Observation of Varroa destructor behavior in capped worker brood of Africanized honey bees - Calderón, Rafael A. (2012)
The behavioral activity of Varroa destructor was observed using transparent cells. Mite oviposition started at 45.0 ± 25.0 h post capping, followed by the next eggs laid at regular 27.3 ± 2.0 h intervals. On the prepupa, mites were found to feed often and there was no preference for a specific segment as a feeding site. During the pupal stage the mite fed less often and almost always at the same point. Varroa showed a preference for defecation in the posterior part of the cell. A significant association was observed between the position of the feeding point in the pupa and the defecation site on the cell wall. Displacement behavior was observed in 71 % of the infested bee larvae and a major change in the free space available for varroa in the cell occurred when the prepupa molted into a pupa.